VISUALIZATION AND REALITY IN PACKAGED BEVARAGE ADVERTISING - Setyawan, Denny Hendrifika (Capture : Jurnal Seni Media Rekam, 2023)
Visual and audio advertising media as information broadcast to audiences must consider advertising ethics because bombastic and manipulative visualizations and narrative sentences deceive the public by providing untruthful information. According to advertising ethics, ontology, and epistemology studies, revising the media’s presentation of product advertisements is imperative. Accordingly, this study utilizes a descriptive-quantitative method based on previous studies and direct observation of the "Adem Sari Chingku Sparkling" advertisement in 2017. Conclusions are drawn using the constructivism method. The results suggest that the presentation of "Adem Sari Chingku" advertisements in the modern era tends to be manipulative. The advertisements are presented with bombastic visuals and biased narratives to manipulate suggestions and lead the audience to develop certain assumptions about the advertisement. The suggestions made by the advertising media do not refer to the composition of the product's raw materials. The audience is led to believe that the product can relieve and cure heartburn.